Lattice Energy of II-VI and III-V Binary Solids and I-VII Ioniccrystals: Exploring the Empirical Relationship between Lattice Energy and Lattice Constant in II-VI and III-V Binary Solids and I-VII Ionic Crystals (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper, we'll look at, an interesting empirical relationship has been proposed to calculate the lattice energy of II-VI and III-V semiconductors and I-VII ionic crystals using their lattice constant. We have applied the proposed empirical relation for the calculation of lattice energy on the binary tetrahedral semiconductors and alkali halides. As applied to other similar theoretical results, the accessible experimental values show outstanding consensus. The lattice energy (in Kcalmol) When these materials are plotted, they display a linear association against the tattice constant (in A), which lies at the straight line. The trial values for lattice energy vary the following quantities Be0- 0.23, BeS-0.639, BeSe-0.0, BeTe-0.78, ZnO-1.75, ZnS-0.10, ZnSe-0.3496, ZnTe-1.46. CdS-0.35, CdSe-1.12, CdTe-0.53, MgTe-1.3, BP-0.09, BAs-0.29, AlN-1.09. AIP 0.80, AIAs-0.79, AlSb-0.16, GaN-0.35. GaP-0.90, GaAs-0.39, GaSb 0.16, InN-0.12, lnP-0.26, InAs-0.13. InSb-0.11. LiF-4.86, LiCl-4.06 LiBr-0.58, Lil-2.37, NaF-2.78, NaCl-1.12, NaBr-1.84, NaI-1.07, KF-2.01. KCl-1.70, KBr-2.61, KI-2.97, RbF-1.48, RbCl-2.56. RbBr-3.51 and Rbl-3.82 the latest studies.